2004
DOI: 10.1088/0953-2048/17/12/011
|View full text |Cite
|
Sign up to set email alerts
|

The development of Y Ba2Cu3Ox thin films using a fluorine-free sol–gel approach for coated conductors

Abstract: Despite great success in the TFA methods of depositing YBa 2 Cu 3 O x (YBCO) thin films for coated conductors, critical issues involved in removing BaCO 3 have not entirely been settled. There could be other possible ways of dealing with carbon that remains in the film. We have recently developed a fluorine-free sol-gel synthesis with several important advantages including precursor solution stability, improved film density, and elimination of HF during processing. With this approach, high-quality YBCO films h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As a consequence, several modified Pechini routes have been developed as alternatives (Bubendorfer et al 2003), where the formation of barium carbonate can also be avoided (Cui et al 2009). The typical cation precursors are nitrates or acetates, but there is a larger variety in the choice of complexing agents, with CA and EG (Cui et al 2009), EDTA (Brylewski and Przybylski 1993), triethanolamine and acetic acid (Thuy et al 2009) and trimethylacetate and propionic acid (Shi et al 2004) all being applied. Bubendorfer et al investigated several organic acid, such as lactic, tartaric, glycolic, malonic and diglycolic acid, but found that malic acid was the best choice, due to its superior ability to chelate Y 3+ (Bubendorfer et al 2003).…”
Section: Superconducting Thin Filmsmentioning
confidence: 99%
“…As a consequence, several modified Pechini routes have been developed as alternatives (Bubendorfer et al 2003), where the formation of barium carbonate can also be avoided (Cui et al 2009). The typical cation precursors are nitrates or acetates, but there is a larger variety in the choice of complexing agents, with CA and EG (Cui et al 2009), EDTA (Brylewski and Przybylski 1993), triethanolamine and acetic acid (Thuy et al 2009) and trimethylacetate and propionic acid (Shi et al 2004) all being applied. Bubendorfer et al investigated several organic acid, such as lactic, tartaric, glycolic, malonic and diglycolic acid, but found that malic acid was the best choice, due to its superior ability to chelate Y 3+ (Bubendorfer et al 2003).…”
Section: Superconducting Thin Filmsmentioning
confidence: 99%
“…The flat features are the typical c-axis oriented YBCO grains from the MOD process. The terrace surface structure with some outgrowths and a few voids are common characteristics of solution-derived films [10,12]. When the BZO content x ≥ 0.12, the YBCO film displays large holes and a rough surface that may decrease the grain connections and homogeneity of the YBCO phase.…”
Section: Optimizing the Bzo Contentmentioning
confidence: 99%
“…It is therefore of interest to develop solution processes where HF evolution is eliminated or greatly reduced. There are some low-fluorine [7,8] and fluorine-free (F-free) precursors [9][10][11][12][13][14] that have been prepared for this purpose. One of these F-free processes is an acetylacetonate (AcAc) solution-based MOD technique, originally developed by the National Institute of Advanced Industrial Science and Technology (AIST) [15][16][17] and used by Sumitomo Electric Industries [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the hydroxides route Ba(OH) 2 and Y-and Ba-trimethylacetates are reacted in propionic acid with amine solvent. Remarkably, it has been reported that this stock solution is stable in air and has a shelf life longer than 2 years [34][35][36]. On the other hand, the CSD based on nitrates, which is also known as polymer-assisted deposition (PAD) because of the use of polymers, obtains a homogeneous distribution of the metal precursors in the solution and the formation of uniform metal-organic films [37].…”
Section: Free-trifluoroacetate Csd Routesmentioning
confidence: 99%